The epidemiology of common mental disorders in Libya: a systematic review - Mansour Abdulshafea (SpringerOpen, 2021)
Abstract Introduction There has been a global increase in the prevalence of common mental disorders (CMD), particularly in conflict hotspots. The limited amount of resources is one of the key barriers to effective treatment within Low- and Middle-income countries (LAMICs). The lack of service provision for mental health disorders in LAMICs has resulted in limited opportunities to conduct mental health research. Libya is a North African country that has suffered from ongoing conflict with the current political unrest in Libya further impacting the mental health of the population. Main text The aim of this review is to conduct a synthesis of evidence regarding the estimated prevalence and associated risk factors of CMD in Libya. A search was completed in the academic databases; PubMed, Medline, EMBASE, PsychINFO, CINHAL, and the Institute for Development, Research, Advocacy and Applied Care (IDRAAC) from inception to March 2020. Only studies that investigated prevalence and associated risk factors of CMD in Libya were included. A total of 219 studies were identified of which 15 met the inclusion criteria for the review. There were (n = 3) papers investigated the prevalence of depression, (n = 4) studies were focused on stress-related disorders and the remaining papers looked at both anxiety and depression. Statistically, sample sizes of the included studies ranged from (n = 41–13,031) for the prevalence studies (mean = 1188.6, median = 233). Conclusion The status of Libya as a conflict hotspot has led to a reduced level of epidemiological data on mental health, with a vital need to conduct research in CMD. Libya requires better clinical governance which can allow for more scientific research into CMD and enabling the Libyan government to develop evidence-based policy initiatives for CMD.